2015
DOI: 10.1007/s00415-015-7924-z
|View full text |Cite
|
Sign up to set email alerts
|

Strictly monitored exercise programs reduce motor deterioration in ALS: preliminary results of a randomized controlled trial

Abstract: The objective of our study was to perform a randomized controlled trial (RCT) aimed to evaluate the effects of three strictly monitored exercise programs(SMEP) compared to "usual care" (UCP) in a cohort of ALS patients. We included patients with definite and probable ALS and disease duration ≤24 months. Patients were randomized to receive a SMEPs or a UCP. SMEPs included three subgroups of treatment: active exercises associated with cycloergometer activity (1A), only active (1B) and passive (1C) exercises, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 47 publications
6
71
1
3
Order By: Relevance
“…The same study suggests a change of 20% or greater in the slope of the ALSFRS-R to be clinically meaningful [23], indicating that the resistance training in our study had no attenuating effect; rather it might have had a worsening effect. This observation differs from three previous studies, reporting positive effects on ALSFRS-R scores following resistance training using different regimes [911]. In one of these studies the training period was 6 months rather than 12 weeks as in our study.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…The same study suggests a change of 20% or greater in the slope of the ALSFRS-R to be clinically meaningful [23], indicating that the resistance training in our study had no attenuating effect; rather it might have had a worsening effect. This observation differs from three previous studies, reporting positive effects on ALSFRS-R scores following resistance training using different regimes [911]. In one of these studies the training period was 6 months rather than 12 weeks as in our study.…”
Section: Discussioncontrasting
confidence: 96%
“…Previous studies using progressive resistance training programs similar to the present have proven effective in improving muscle strength and functionality in frail older individuals [2, 4, 24]. Resistance training interventions in ALS patients reporting positive results have used individualized moderate-intense exercises yet without providing more specific details on the exercises, intensity, progression, and so on [6, 911]. These aspects probably explain some of the discrepancy in previous findings compared to the present findings, along with the heterogeneity and size of the ALS study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small, randomized trial, resistance exercise improved patient outcomes when measured using the ALS Functional Rating Scale (ALSFRS-R) and upper and lower extremity subscale scores [311]. Another randomized controlled trial of exercise in ALS showed no benefits to survival or quality of life, but did report a positive outcome for the ALSFRS-R score [312]. A recent review of exercise trials for ALS has concluded more studies are needed to determine the risks and benefits of exercise in ALS [313].…”
Section: Mitochondrial Medicine In Alsmentioning
confidence: 99%
“…The most recent Cochrane review on the topic points out the need for more rigorous randomized controlled trials (RCT) while acknowledging the moderate benefit of exercise and lack of reported adverse effects in existing RCTs [14]. Since that review, but prior to our survey, two trials have been completed that found a moderate intensity (60% of maximal power output) exercise program reduced the rate of motor deterioration in pALS [15] and that resistance and endurance exercise are safe for pALS [16]. While the evidence for modest beneficial effects of exercise on the progression of ALS accumulates, the lack of reported adverse effects in RCTs is consistent.…”
Section: Introductionmentioning
confidence: 99%